2010
DOI: 10.1002/da.20755
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the magnitude of biased attention in depression

Abstract: In this quantitative review, we examined the magnitude of attentional biases to negative stimuli in depression. Results from 29 empirical studies examining emotional Stroop or dot probe results in depressed participants (clinical depression, nonclinical dysphoria, and subjects undergoing depressive mood induction) were examined. Studies using the emotional Stroop task yielded marginally significant evidence of a difference between depressed and nondepressed samples, whereas those using the dot probe task showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
377
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(417 citation statements)
references
References 156 publications
(218 reference statements)
34
377
3
3
Order By: Relevance
“…1 A recent meta-analysis showed that depressed samples (i.e., encompassing dysphoric, clinically depressed, and remitted depressed individuals) exhibit an attention bias favoring negative information and also an absence of a positivity bias, compared with nondepressed samples (Peckham, McHugh, & Otto, 2010). Specifically, selective attention for negative information is characterized by impaired disengagement of attention from the processing of negative information rather than enhanced engagement with negative information .…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…1 A recent meta-analysis showed that depressed samples (i.e., encompassing dysphoric, clinically depressed, and remitted depressed individuals) exhibit an attention bias favoring negative information and also an absence of a positivity bias, compared with nondepressed samples (Peckham, McHugh, & Otto, 2010). Specifically, selective attention for negative information is characterized by impaired disengagement of attention from the processing of negative information rather than enhanced engagement with negative information .…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Emotional biases in attention are related to psychological well-being: Healthy individuals pay more attention to positive material, whereas anxious and depressed individuals predominantly attend to threatening or sad material (Peckham, McHugh, & Otto, 2010;Van Bockstaele et al, 2014). These attention biases operate at several stages in the pathogenesis of affective disorders (e.g., at subclinical or remission stages), affect an individual's response to emotionally distressing situations, and predict the course of affective symptoms over time (Cisler, Bacon, & Williams, 2009;De Raedt & Koster, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given the low cortisol levels that characterize the postpartum period, it is conceivable that the endocrine milieu also may have contributed to our finding. Finally, previous research has suggested that attentional bias is influenced by depression severity and comorbid anxiety (Cisler et al., 2011; Epp et al., 2012; Peckham et al., 2010). Greater effect sizes are noted in samples with clinical depression than in samples with depressed mood (Epp et al., 2012), and similarly, greater effect sizes are noted in cases with comorbid anxiety and depression than in cases who only suffer from depression (Epp et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Attentional bias in this context is typified by longer latency (emotional interference) to name the color of affectively valenced words as compared with neutral ones. Attentional bias to negative stimuli has relatively consistently been reported in patients with depressive disorders (Cisler et al., 2011; Epp, Dobson, Dozois, & Frewen, 2012; Peckham, McHugh, & Otto, 2010), but seem to depend on the severity of the depressive episode, thus being more commonly found in patients with clinical depression and in patients with comorbid anxiety than in patients who merely present with depressive symptoms (Epp et al., 2012; Lyche, Jonassen, Stiles, Ulleberg, & Landro, 2011; Markela‐Lerenc et al., 2011). In addition, patients with depressive episodes may also present with attentional bias to positive stimuli in the emotional Stroop task, or lack of differentiation between the positive and negative stimuli (Epp et al., 2012; Gotlib & Joormann, 2010), or even with attentional bias away from emotional stimuli (Zvielli, Vrijsen, Koster, & Bernstein, 2016).…”
Section: Introductionmentioning
confidence: 99%